Wideband Negative Permittivity and Double Negative Fishnet-Mushroom-Like Metamaterial in X-Band Waveguide - Ahmed Mahmood; Golge Ogucu Yetkin; Cumali Sabah (Advances in Condensed Matter Physics)
A Fishnet-Mushroom-like metamaterial electromagnetic behaviour is represented in S-parameters numerically and experimentally for X-band frequencies arena. The design has introduced a dielectric substrate as a host with metallic parts. The proposed design is predicted to provide the electromagnetic band gap characterization with desired reiterative characteristic parameters, negative permittivity, and negative permeability exhibiting a double negative left-handed region, which is identified with the X-band regime with good agreement between the simulated and the measured results.